Pain and psychological readiness to return to sport in elite volleyball players: a cross-sectional study - Gajardo-Burgos, R.; Valdebenito-Tejos, C.; Gálvez-García, G.; Bascour-Sandoval, C. (International Journal of Environmental Research and Public Health, 2023)
Pain is modulated by multiple factors. A relevant psychological process peculiar to athletes and which could be associated with pain is Psychological Readiness to Return to Sport (PRRS). The analysis of this association in competition context is particularly important. Objective: To determine the correlation between the PRRS and pain intensity in elite volleyball players during their participation in a continental sporting event. Methods: A cross-sectional study was conducted. Data from 107 male volleyball players (23.50 ± 4.08 years of age) participating in the South American Volleyball Championship were used. The athletes answered a self-report questionnaire on the day the championship began regarding their history of injuries in the previous six months. The athletes who declared injuries were asked about the current pain intensity using the Pain Numeric Rating Scale (NRS) and Psychological Readiness to Return to Sport using the Injury-Psychological Readiness to Return to Sport scale (I-PRRS). Results: 43.93% (n = 47) of the athletes (23.70 ± 3.54 years) reported an injury in the six months prior to the championship. They presented a median on the NRS of three (interquartile range (IQR), 2-5), and 54 (IQR, 46-58) on the I-PRRS. The Spearman`s Rho correlation test showed an inversely and moderate correlation (rs = -0.36; p = 0.011; CI: -0.64--0.08) between pain intensity and PRRS. Conclusion: In male elite volleyball players who participate in a Continental Championship in South America, higher levels of PRRS was correlated to lower pain intensity.